EFISIENSI PRODUKSI DAN PRODUKTIVITAS TENAGA KERJA INDUSTRI MIKRO DI INDONESIA - Asrizal SE, M.Si (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
This research aims to determine the efficiency of production and labor productivity inmicro industries in Indonesia. Research using descriptive method, the data used while thedata output value and the value of labor expenditure on micro industries. The analysistechnique used to answer the purpose of using the Cobb-Douglas production function.Data analysis showed that production efficiency is higher in 2015 than in 2013, while thelabor productivity in 2013 was higher than in 2015.Key Word: The added value, production efficiency and labor productivity